Forest in a changing world - Markham, John (2016)
Forest ecosystems have been used for human populations over millennia. Even today, forests provide a large amount of resources and environmental services for modern human populations, but disturbance caused by human activities has altered and threatened these ecosystems across the globe. Forests are distributed over a large span of latitudes and elevations, and as a response, there is large variability in their characteristics. Different kinds of forest vary in their structure, species composition, patterns of diversity, patterns of disturbance, and regeneration. Here we explore the characteristics of gymnosperm and angiosperm-dominated forests, and explore the ecological characteristics of three main forest biomes: boreal, temperate, and tropical forests in terms of productivity and structural and species diversity. Finally, we explore fine scale variability within these ecosystems and the implications of natural and human disturbance on these environments.